2019
DOI: 10.1007/s10567-019-00277-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of Child (0–5 Years) Outcome Measures as used in Randomized Controlled Trials of Parent Programs: A Systematic Review

Abstract: This systematic review is one of the three which sought to identify measures commonly implemented in parenting program research, and to assess the level of psychometric evidence available for their use with this age group. This review focuses specifically on measures of child social–emotional and behavioral outcomes. Two separate searches of the same databases were conducted; firstly to identify eligible instruments, and secondly to identify studies reporting on the psychometric properties of the identified me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 71 publications
(106 reference statements)
1
13
0
1
Order By: Relevance
“…However, from the 18 parent outcome measures reviewed (three measuring parenting attitudes and beliefs, three measuring parenting practices, six measuring general psychological wellbeing, two measuring parent stress, four measuring parent depression), there is not one clear measure that we can definitively recommend for each outcome domain to form a core battery. This is consistent with our reviews assessing child outcome measures (see Gridley et al 2019a) and dyadic measures (see Gridley et al 2019b). Nevertheless, we have highlighted five parent outcome measures (one from each outcome domain) that perform comparatively well in their respective outcome domains; the PSoC (parenting attitudes and beliefs), the Parenting Scale (parenting practices), GHQ-12 (general psychological wellbeing), PSI-SF (parenting stress) and EPDS (parental depression).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, from the 18 parent outcome measures reviewed (three measuring parenting attitudes and beliefs, three measuring parenting practices, six measuring general psychological wellbeing, two measuring parent stress, four measuring parent depression), there is not one clear measure that we can definitively recommend for each outcome domain to form a core battery. This is consistent with our reviews assessing child outcome measures (see Gridley et al 2019a) and dyadic measures (see Gridley et al 2019b). Nevertheless, we have highlighted five parent outcome measures (one from each outcome domain) that perform comparatively well in their respective outcome domains; the PSoC (parenting attitudes and beliefs), the Parenting Scale (parenting practices), GHQ-12 (general psychological wellbeing), PSI-SF (parenting stress) and EPDS (parental depression).…”
Section: Discussionsupporting
confidence: 92%
“…Findings specifically relating to parent outcome measures for RQ2 are also presented. Child outcome measures reviewed in response to RQ2 are reported in the second review (Gridley et al 2019a), and the results of our appraisal of dyadic (parent–child relationship) outcome measures are presented in the third review (Gridley et al 2019b). This study was registered with PROSPERO, an international database of prospectively registered systematic reviews in health and social care housed by the University of York’s Centre for Reviews and Dissemination (CRD).…”
Section: The Current Studymentioning
confidence: 99%
“…This is a practitioner-administered assessment that can be used on children from birth to 68 months. 71 Although the MSEL has been reported to have high interrater reliability (range: 0.91-0.99) and good construct and criterion validity in a normative population, 72 there is limited information regarding its sensitivity and specificity. More research on the psychometrics of the MSEL is needed to determine its appropriateness as a gold standard assessment tool for the measurement of motor function in at-risk children between 0 and 24 months.…”
Section: Gross Motormentioning
confidence: 99%
“…A very limited number of brief parent self-report tools exist that assess maternal-infant bonding, are freely available, and have some reliability and validity (Blower et al, 2019; Gridley et al, 2019; Kane, 2017; Wittowski et al, 2020), for example; Maternal Attachment Inventory (MAI; Müller, 1994); Maternal Postnatal Attachment Scale (MPAS) (Condon and Corkindale, 1998); Postpartum Bonding Questionnaire (PBQ) (Brockington et al, 2006); Mother Infant Bonding Scale (MIBS) (Taylor et al, 2005). However, most are not widely used, or have been validated with a small sample (for further discussion see Wittowski et al, 2020; Le Bas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, most are not widely used, or have been validated with a small sample (for further discussion see Wittowski et al, 2020; Le Bas et al, 2019). A further two reviews, Blower et al, 2019 and Gridley et al, 2019 were undertaken to explore which measures would be acceptable, reliable, and valid for a large randomised controlled trial of a parenting intervention for parents of infants and toddlers and it was found that choice of measures was very limited (the trial was led by TB, the first author. For the protocol see Bywater et al, 2018).…”
Section: Introductionmentioning
confidence: 99%